Trinity Cathedral from the south, Port-of-Spain, Trinidad, B.W.I. - (:unkn) unknown (The Bonanza, Smith Bros and Co., Trinidad, 2010)
Image depicts a view of the Trinity Cathedral, located in the capital city of Port of Spain, in the Republic of Trinidad and Tobago. This is a view of the southern elevation of the building from upper Chacon Street, looking northward.
Style: Landscape; Colour: Black and White; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals; Buildings